PENGARUH KECEMASAN MAHASISWA DAN DUKUNGAN KELUARGA TERHADAP PROSES PENYUSUNAN SKRIPSI DI UNIVERSITAS PGRI BANYUWANGI - Harwanti Noviandari; Raup Padillah; Dody Nugroho (BIMBINGAN DAN KONSELING BANYUWANGI, 2022)
The aims of this study are 1. To measure anxiety that can affect students in the process of writing a thesis at PGRI Banyuwangi University. 2. To measure family support can influence students in the process of writing a thesis at PGRI Banyuwangi University. 3. To measure anxiety and family support can affect students in the process of writing a thesis at PGRI Banyuwangi University. This study uses descriptive quantitative data collection using observation and questionnaires. The population in this study were all final year students at PGRI Banyuwangi University and a sample of 30 students. In taking the sample using the Proportional Sampling technique. The data analysis technique in this study uses the product moment correlation technique. The results showed that the effective contribution of the anxiety variable and family support to the thesis preparation process was 84.2%. So that there are 15.8% of other variables that affect the preparation of the thesis other than the two X variables studied. Variables that may influence the preparation of the thesis are emotional, individual/group conflicts, communication and so on.